2010
DOI: 10.1016/j.electstud.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Measuring party nationalisation: A new Gini-based indicator that corrects for the number of units

Abstract: The study of the territorial distribution of votes in elections has become an important field of the political party research in recent years. Quantitative studies on the homogeneity of votes and turnout employ different indicators of territorial variance, but despite important progresses in measurement, many of them are sensitive to size and number of political parties or electoral districts. This article proposes a new 'standardised party nationalisation score', which is based on the Gini coefficient of ineq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
122
0
16

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(139 citation statements)
references
References 24 publications
1
122
0
16
Order By: Relevance
“…Nevertheless, many measures still have potential shortcomings that might lead to problematic outcomes when different parties or party systems shall be compared (see Caramani, 2004;Bochsler, 2009, for an overview). Many measures are insensitive to transfers of votes from one party to another, they weight large and small districts equally, Therefore, for the operationalisation of my dependent variable, I employ the standardised party nationalisation score (Bochsler, 2009), which accounts for the mentioned problems.…”
Section: Cases and Operationalisationmentioning
confidence: 99%
“…Nevertheless, many measures still have potential shortcomings that might lead to problematic outcomes when different parties or party systems shall be compared (see Caramani, 2004;Bochsler, 2009, for an overview). Many measures are insensitive to transfers of votes from one party to another, they weight large and small districts equally, Therefore, for the operationalisation of my dependent variable, I employ the standardised party nationalisation score (Bochsler, 2009), which accounts for the mentioned problems.…”
Section: Cases and Operationalisationmentioning
confidence: 99%
“…To define the overall territorial differences, I conducted a hot spot analysis from the spatial statistics methodology (Bochsler 2010, Dusek-Kotosz 2016, Tóth 2003. Adopting this methodology, other research has shown the distortions of constituencies, territorial differences in party preferences, and the impacts on political representation (Vida-Kovács 2015).…”
Section: Zoltán Bertusmentioning
confidence: 99%
“…The process of nationalization of a party would mean, therefore, a territorial penetration of some sort, so that the partisan distribution across a given country in a given election would become increasingly homogeneous. After Schattschneider, such interpretation gained popularity, being more recently adopted by a number of important works (e.g Sundquist, 1973;Rose and Urwin, 1975;Lee, 1988;Jones and Mainwaring, 2003;Caramani, 2004;and Chhiber and Kollman, 1998, Bochsler, 2010.…”
Section: Multiple Nationalizationsmentioning
confidence: 99%
“…This measure has many advantages. First, the Gini index and its interpretation are well known, unlike most other common options for assessing party nationalization (for a comprehensive list Registered parties / Legend: countrywide elec.support: Weighted territorial homogeneity of membership rates of these options, see Caramani, 2004 andBochsler, 2010). It assess precisely what we want, which is territorial homogeneity versus heterogeneity, of the quantities of interest.…”
Section: Nationalization Of Organizationmentioning
confidence: 99%
See 1 more Smart Citation